A case study of physical and social barriers to hygiene and child growth in remote Australian Aboriginal communities - Grace Jocelyn; Bailie Ross; McDonald Elizabeth; Brewster David (BMC, 2009)
Abstract Background Despite Australia's wealth, poor growth is common among Aboriginal children living in remote communities. An important underlying factor for poor growth is the unhygienic state of the living environment in these communities. This study explores the physical and social barriers to achieving safe levels of hygiene for these children. Methods A mixed qualitative and quantitative approach included a community level cross-sectional housing infrastructure survey, focus groups, case studies and key informant interviews in one community. Results We found that a combination of crowding, non-functioning essential housing infrastructure and poor standards of personal and domestic hygiene underlie the high burden of infection experienced by children in this remote community. Conclusion There is a need to address policy and the management of infrastructure, as well as key parenting and childcare practices that allow the high burden of infection among children to persist. The common characteristics of many remote Aboriginal communities in Australia suggest that these findings may be more widely applicable.